On the Concept of Globality - Brienza, Paul (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2015)
It is a common claim, in this day and age, that the world is becoming more and more ‘globalized.’ However, very little attention is paid to the larger consequences and implications of a globalized world. In this issue of Theoria and Praxis contributors explore the deep meanings of globality in light of the facts of economic integration, political interdependency and cultural convergence.